Prevalence and risk factors associated with psychostimulant use among Black individuals: A meta-analysis and systematic review. (March 2023) - Cénat, Jude Mary; Kogan, Cary S.; Kebedom, Philmona; Ukwu, Gloria; Moshirian Farahi, Seyed Mohammad Mahdi; Darius, Wina Paul; Mulopo Bakombo, Schwab; Dalexis, Rose Darly; Ndengeyingoma, Assumpta; Noorishad, Pari-Gole; Labelle, Patrick R.
Highlights: More than one out of 10 (11.4%) Black individuals living in minority contexts have used psychostimulants. The prevalence of lifetime use of cocaine (12.4%), amphetamine (8.3%) and other stimulants (11.4%) was high in Black communities. Important gaps still exist and data on psychostimulants and gender, level of education, area inhabited need to be collected. Data should also be collected on psychostimulants according to experiences of discrimination. Given the broad range of prediction intervals future studies should explore explaining individual and social factors. Case-control studies might be conducted to determine what causes Black people in minority contexts to use or not use substance. Abstract: Background: Psychostimulants (e.g., cocaine, amphetamine) are among the most widely used drugs globally with detrimental short and long-term physical, psychological and social consequences. There is limited data on psychostimulant use for various racial and ethnic groups, including Black people, and the challenges they face living as minorities overcoming historical challenges including increased incarceration associated with drug possession. Methods: Peer-reviewed articles were identified in five databases (APA PsycInfo, CINAHL, Cochrane CENTRAL, Embase, MEDLINE). Eligible studies were published in French or English, provided empiral data on psychostimulant use in Black individuals living in a minority context. The PRISMA guideline was used for structuring the review. Random-effects meta -analyses were generated to estimate the pooled prevalence of lifetime and periodic psychostimulant use among Black individuals using STATA 16. Results: Sixty-three studies published from 1991 to 2022 with a sample size of 139, 683 Black individuals were included in the current meta -analysis. Results indicate a pooled prevalence estimate of 11.4% for any form of psychostimulant use among Black individuals. The pooled prevalence estimates were 12.4% (95% CI, 8.4% − 16.4%) for cocaine, 8.3% (95% CI, 0% − 19.1%) for amphetamines, and 11.4% (95% CI, 4.6% − 18.1%) for other stimulants. Prediction intervals for all psychostimulant types were highly heterogenous ranging from 0% to as high as 51.2% for amphetamine suggesting prevalence of use in some studies of Black people could be found to be as low as zero. Subgroup analyses were conducted to examine differences between age groups, gender, reference period, and type of assessment. Conclusions: High prevalence rates of psychostimulant use among Black people argues for greater access to evidence-based treatments. However, current psychosocial interventions are suboptimal, warranting further study. Consideration needs to be given to the challenges of the large range of prediction intervals, living in urban areas, racial discrimination experiences, race-based stress, and sociodemographic characteristics, including poverty, education level, age, gender.